Pelaksanaan Program Tahfidz Al-Qur’an di MAN 2 Palembang - Dwiyana, Annisa; Niswah, Choirun; Ibrahim, Ibrahim (Indo-MathEdu Intellectuals Journal, 2024)
The aim of this research is to understand the implementation of the tahfidz program at MAN 2 Palembang and to identify the supporting and inhibiting factors during the implementation of the Qur’an memorization program at MAN 2 Palembang. This research employs a qualitative research method, and the informants include the head of the madrasa, the head of the Darul Ulum tahfidz house, tahfidz supervisors, and students. The data collection techniques used in this study are observation, interviews, and documentation. The data analysis techniques employed are data reduction, data presentation, and conclusion drawing. The validity of the data is tested using triangulation, which includes source triangulation, technique triangulation, and time triangulation. The results of the research indicate that the tahfidz Qur’an program at MAN 2 Palembang is carried out through direction, motivation, communication, and coordination in each process, starting with determining the program's objectives, defining success indicators, setting the implementation schedule, and appointing program coordinators. The supporting factors include adequate facilities and infrastructure, quality human resources, the presence of rewards and punishments, and the program's timing. The inhibiting factors include the students' own attitudes and their surrounding environment